Peran Komite Sekolah dalam Peningkatan Mutu Pendidikan Agama Islam di SMP Swasta Karya Bhakti (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2026)
This study aims to analyze the role of the school committee in improving the quality of Islamic Religious Education at Karya Bhakti Private Junior High School. The research employed a qualitative descriptive approach to gain an in-depth understanding of the committee’s involvement in educational activities. The research subjects consisted of the principal, Islamic Religious Education teachers, and school committee members. Data were collected through observation, interviews, and documentation. The data analysis process included data reduction, data presentation, and drawing conclusions systematically. The findings revealed that the school committee has performed its roles as an advisory, supporting, controlling, and mediating body. The committee contributes to program planning, supports religious activities, supervises implementation, and facilitates communication between the school and the community. However, these roles have not been carried out optimally due to limited participation and weak coordination among stakeholders. As a result, although the school committee plays an important role in enhancing the quality of Islamic Religious Education, improvements are still needed to increase its effectiveness. Strengthening collaboration, improving coordination, and increasing active participation from all members are essential to maximize the contribution of the school committee in supporting educational quality.